House of lost secrets - Harris, Anstey (Lake Union Publishing, 2024)
"She thought she knew her best friend…She was wrong. The weatherworn cottage Clachan has always been Jo Wilding’s sanctuary, a blissful escape from her tumultuous home life. From the first summer Rachel invited her to join the Willoughby family in the wilds of Scotland, she fell in love with the sea air, sandy beach and Tristan, Rachel’s older brother… All these years later, Clachan is where their most important occasions and conversations take place, so when Rachel organises a weekend there, Jo never suspects that this weekend will change everything. Because it turns out Rachel has been keeping a secret, a betrayal that plunges Jo into a past she’s spent years trying to forget. Left to untangle the pieces of their past alone, Jo has to decide if there is such a thing as forgiveness when there is no one left to forgive?" -- Amazon.